Trade with Historical Hunting Rifles Based on an Investment Fund - Benda, Lukáš; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
Passion for collectibles dates back to the primal ages and is not solely limited to humans. Hunting firearms collecting dates back to modern-day Austria and with the growing wealth in the society its collection became a widespread practice, and a passion of many. The diploma thesis researches viability and feasibility of trade with historical rifles through an investment fund and its vital operational and establishment processes. Basis of this research is a combination of a primary and secondary research, where interviews with professionals involved in investment fund and firearms industry were conducted. The thesis aims to provide practical overview of the legal background and processes involved within the establishment and operations of the investment fund. As a result of the research, a scheme with a selected form of an investment fund is provided including a step by step description of purchase process of historical hunting firearm from a foreign auction house.
Vedoucí práce: Jaroslav Halík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses